Influence of Circadian Disruption Associated With Artificial Light at Night on Micturition Patterns in Shift Workers - Kim, Su Jin (Int Neurourol J, 2019)
Shift workers often experience problems associated with circadian disruption associated with artificial light at night and nocturia is commonly noted in night-shift workers. Nocturia associated with circadian disruption is due to increased urine production of the kidney and decreased storage function of the bladder. A recent discovery of peripheral clock genes in the bladder and their role in contractile property of the bladder support that micturition is closely related to the circadian rhythm. Moreover, there are clinical studies showed that shift workers more often experienced nocturia due to circadian disruption. However, comparing with other health problems, concerns on nocturia and voiding dysfunction associated with circadian disruption are insufficient. Therefore, further studies about voiding dysfunction associated with the circadian disruption in shift workers are necessary.